A reflection on the poems of José Ribeiro Escoba (TEL Tempo, Espaço e Linguagem, 2022)
This article aims to reflect on the importance of José Ribeiro Escobar's poems, as a way of expressing the political, social and economic contexts of the first decade of the 20th century. Brazilian society was going through significant urban transformations, which aimed to illuminate and civilize public spaces with a view to modernity, removing the remnants of the Empire and reflecting the urban-industrial dimension. In this environment, the school was configured as a means of civilizing, propagating that discipline and order were necessary for the nation to exist. Escobar sought meaning for Brazilian education, defending public instruction, the teacher and his pedagogical conceptions regarding teaching methods. He had a strong participation in Brazilian education, however, he called himself only with an educator and poet, who loved his country. Escobar added the list of intellectuals and experts who discussed the educational field at the beginning of the 20th century, alongside other identically influential educators. Escobar published his poems in order to reaffirm his convictions about Brazilian education. For him, the school should allow students to experience practical experiences through concrete materials, with a view to psychological, physical, educational, social and moral training. It is essential to educate students to become true Brazilian citizens. His poems were not impartial, but they reflected civic-patriotic movements, the needs and the very organization of society.